Auctions and mechanism design for decentralized marketplaces - Maree, Christopher (Graduation School of Business, 2022)
Those that come up with commercially viable ideas are often not the best suited to implement them. This can lead to allocational inefficacy in the deployment of good ideas. The transfer or licensing of patents is a means of commercializing ideas. However, in the current patent market, the idea seller and the idea buyer often don't match which results in the proliferation of adverse selection. This thesis examines the existing patent market and finds many examples of opacity. Pitfalls abound for both sellers and buyers which result in inefficiencies when attempting to find the best fit for seller and buyer. Improvements in allocating ideas to the best implementers would help inventors and companies alike. Brilliant ideas are frequently generated from universities. This thesis presents a means to commercialize these ideas by issuing licenses on the blockchain in an innovative marketplace for ideas. This commercialization of ideas generates funds that support the institution that originally conceived the ideas and indirectly supports foundational research. The marketplace for ideas is based on sealed bid auctions which ensure that the company that values the idea the most is allocated the license. An optional Harberger Tax system is included to generate constant revenue for the universities from the licensed ideas. This mechanism decreases information asymmetries, increases market liquidity and provides representative license pricing. Smart contracts deployed on the Ethereum blockchain are used to eliminate auction corruption through trustless sealed bid auctions. Smart contracts also automate license issuance, payments and act as a public ledger of license ownership and provenance. A full front-end web application is presented to interface with the marketplace for all users.